Penatalaksanaan Holistik Pasien Anak Laki - Laki Usia 3 Tahun Dengan Skabies Melalui Pendekatan Kedokteran Keluarga Di Puskesmas Tanjung Sari Natar - Muhammad Gusti Fawwaz; Listiani, Farida (CV. Jasa Sukses Abadi, 2025)
Scabies is a skin disease caused by an infestation that can be transmitted through direct or indirect contact. This condition can become chronic and lead to complications; therefore, appropriate and holistic management is necessary using a family medicine approach to achieve successful therapy. The aim of this study is to identify the internal and external risk factors and clinical problems present in the patient, to apply a holistic and comprehensive family physician approach based on the issues identified, and to carry out management based on Evidence-Based Medicine that is family-approach, patient-centered, and community-oriented. This study is a case report. Primary data were obtained through anamnesis, physical examination, and home visits. Secondary data were obtained from the patient's medical records. The patient, F, a 3-year-old child, presented with the main complaint of itching on the hands, feet, and body for the past two months. Internal risk factors for the patient included poor personal hygiene, a sibling with a history of scabies, a curative treatment pattern, and a lack of knowledge about the causes, risk factors, complications, prevention, transmission, and treatment of scabies. External risk factors included the family's lack of knowledge about the patient’s illness, its risk factors, complications, prevention, transmission, and treatment. Diagnosis and management of the patient were carried out in a holistic, patient-centered, family-focused, and community-oriented manner. Clinical improvements, as well as increased knowledge and behavioral changes in the patient and their family, were observed following the intervention.